Concurrent evolution of cancer cachexia and heart failure: bilateral effects exist. Issue 2 (14th March 2014) - Kazemi‐Bajestani, Seyyed M. R.; Becher, Harald; Fassbender, Konrad; Chu, Quincy; Baracos, Vickie E.
Abstract : Cancer cachexia is defined as a multifactorial syndrome of involuntary weight loss characterized by an ongoing loss of skeletal muscle mass and progressive functional impairment. It is postulated that cardiac dysfunction/atrophy parallels skeletal muscle atrophy in cancer cachexia. Cardiotoxic chemotherapy may additionally result in cardiac dysfunction and heart failure in some cancer patients. Heart failure thus may be a consequence of either ongoing cachexia or chemotherapy‐induced cardiotoxicity; at the same time, heart failure can result in cachexia, especially muscle wasting. Therefore, the subsequent heart failure and cardiac cachexia can exacerbate the existing cancer‐induced cachexia. We discuss these bilateral effects between cancer cachexia and heart failure in cancer patients. Since cachectic patients are more susceptible to chemotherapy‐induced toxicity overall, this may also include increased cardiotoxicity of antineoplastic agents. Patients with cachexia could thus be doubly unfortunate, with cachexia‐related cardiac dysfunction/heart failure and increased susceptibility to cardiotoxicity during treatment. Cardiovascular risk factors as well as pre‐existing heart failure seem to exacerbate cardiac susceptibility against cachexia and increase the rate of cardiac cachexia. Hence, chemotherapy‐induced cardiotoxicity, cardiovascular risk factors, and pre‐existing heart failure may accelerate the vicious cycle of cachexia‐heart failure. The impact of cancer cachexia on cardiac dysfunction/heart failure in cancer patients has not been thoroughly studied. A combination of serial echocardiography for detection of cachexia‐induced cardiac remodeling and computed tomography image analysis for detection of skeletal muscle wasting would appear a practical and non‐invasive approach to develop an understanding of cardiac structural/functional alterations that are directly related to cachexia.